Perfil histoquímico e composição da parede celular durante o desenvolvimento de galhas induzidas por Bystracoccus mataybae (Eriococcidae) em Matayba guianensis (Sapindaceae) - Silva, Ana Flávia de Melo (2019)
Bystracoccus mataybae (Eriococcidae, Hemiptera) induce galls on Matayba guianensis Aubl. (Sapindaceae), an abundant plant species of the Cerrado. The galling insect is parthenogenetic and has three instars throughout its development, all of them occurring on the same host in a synchronized cycle. Stem galls are induced by first instar nymphs (crawlers) at the dry season. When the leaf sprouting begins, the second instar nymph moves to the leaflets to induce a new gall cycle. At the leaflets, the second nymph becomes adult, gets pregnancy and die after the crawlers get out of the leaflet galls and move to stem. Thus, the objective of the study was to understand the dynamics of the structural and chemical components in Matayba guianensis galls. The structural and chemical study in different insect stages revealed that galls induced by the first instar nymph of B. mataybae in stem presented low complexity compared to leaflet galls induced by the second instar nymphs. The compartmentalization of the primary and secondary compounds was determined early by the second instar nymph at the beginning of leaflet gall development, and they change little during the other stages of the galling insect. Changes were observed in the pectic and protein cell wall composition from non-galled leaflet to gall and during gall development. Pectins with different methyl esterification degrees were more present in young galls. The lignification process started in young galls and seems to be related not only as mechanism of stress dissipation but also assist in the growth and stretching of the cell wall. Thus, all the structural and chemical changes in M. guianensis galls occur within the morphogenetic potentials of host plant dependent of the induction sites.